Ivanka’s Rhetoric in Defense of Donald Trump’s Political Standing - Stefany Juliwati (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study was to find out about the rhetorical appeals and the prominent forms of persuasions in Ivanka Trump's political speech. The source of the data of this study are texts (both written and spoken) related to Ivanka Trump’s 2020 RNC speech. The data of this study are the verbal speech, gestures, vocal delivery, and facial expression (from the video) as well as words, phrases, and sentences (from the written transcript). In this study, the writer used a qualitative content analysis approach. The theories applied consist of rhetorical appeals and persuasion theory as main theory, supported by the theories of rhetorical styles, rhetorical delivery, and context. The findings reveal that Ivanka used all forms of rhetorical appeals (ethos, pathos, logos) in her 2020 Republican National Convention speech. In addition, 20 forms of prominent persuasions were present in her speech.